Effective electricity cost management in a manufacturing operation by using optimal ETOU tariff formulation / M. F. Sulaima, N. Y. Dahlan and Z. M. Yasin - Sulaima, M. F.; Dahlan, N. Y.; Yasin, Z. M. (Universiti Teknologi MARA, 2019)
In this study, simultaneous Demand Side Management (DSM) strategies are proposed for energy consumption cost reduction and peak load mitigation to industrial’s consumers. By which, a real test case study of a manufacturing electricity load profile had been used to prove the concept. A superior bio-inspired algorithm, Particle Swarm Optimization (PSO) and Ant Colony Optimization (ACO) had been implemented and compared in order to optimize the upright load profile of load management strategy. Subsequently, significant simulation results of operation profit gain through 24 hours power consumption had been analyzed properly. The proposed method had shown reduction of electricity energy consumption cost at all pricing zones; and Maximum Demand (MD) cost mitigation when load management weightages were applied to the identified 10% controlled loads consequently. The investigation has found that, the loads are manageable through the improvement of Load Factor Index (LFI) while Buildings’ Electricity Economic Responsive Index (BEERI) has been the indicator to find the minimum requirement for the optimum load management weightages. Thus, it is hoped that the finding of this study can help to poise the industrial operation in terms of electricity cost effectiveness as well as support the national demand side management program.